ANALISIS KEBUTUHAN MANAJEMEN PENDIDIKAN DALAM PENINGKATAN KUALITAS SEKOLAH DASAR NEGERI 012 PALARAN - Sahmawati; Akhmad Muaddin; M. Eka Mahmud (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the educational management needs at SDN 012 Palaran to formulate strategic quality improvement recommendations. Amid globalization and rapid educational transformations, state elementary schools often encounter budgeting and bureaucratic rigidities that challenge compliance with Graduate Competency Standards (SKL). This study employed a qualitative approach with a descriptive research design. Data were collected through participant observation, in-depth interviews with the principal, teachers, administrative staff, and school committee members, and documentary review. Data analysis followed the interactive model of Miles and Huberman, involving data reduction, data display, and conclusion drawing, validated through source and technique triangulation. The findings indicated that while SDN 012 Palaran possesses strong managerial potential, its management practices tend to be reactive rather than proactive. The school’s readiness in community relations is high, providing a solid social capital. However, curriculum planning and teacher management are moderately developed, and facilities management remains low due to inadequate digital tracking systems. This study concludes that school quality acceleration does not require radical structural transformation but rather systemic optimization through need-based management, prioritizing curriculum digitalization, specific pedagogical training, and digital inventory systems.